Pertinencia del programa académico de la carrera de Ingeniería Agronómica en la región sur del Ecuador - Torres Sarango, Jessenia Fernanda (2015)
This project investigates the academic program that establishes indicators for quality, efficiency and relevance pertaining to the Agricultural Engineering degree program of the National University of Loja. It was implemented as a response to the legal provisions demanded by the Act of Higher Education (AOHE); the Higher Education Council (HEC); the Board of Evaluation Accreditation and Quality Assurance in Higher Education (BEAQAHE) and the Regulation of Academic Systems (RAS). This research was conducted to aid in the Degree Program Redesign thus complying with the new model of university education. To carry out the project, the theoretical aspects, components and regulatory elements that support the Degree Program Redesign in Ecuador were analysed. Then it was proposed to present a situational analysis of the Agricultural Engineering Degree Program based on surveys of graduates from the course, agronomy professionals, employers and interviews. This activity brought together information with respect to the requirements that the productive sector needs and that should be incorporated into the new design of the curriculum of the Agronomy Degree Program. This activity took into account job skills, ingress and egress profiles to add them into the logical network of contents, key subjects to guide the training of future professionals. In this way, a competitive degree program in the formation of Agricultural Engineers would be achieved. It would provide Engineers who were capable of solving problems related to real life local and national agricultural issues, meeting the needs of the population and the services of good living. It would help guarantee the rights of nature and promote innovation to meet new state policies with the change of the productive matrix based on scientific research, technological development and practice ethical and professional values.